Study of Drinking Water Production in Water Treatment Plant “X” using Hazard Analysis Critical Control Point Method - Meralda Rose Dewi; Nieke Karnaningroem; Mas Agus Mardyanto (Institut Teknologi Sepuluh Nopember, 2019)
Water Treatment Plant (WTP) “X” consists of intake, aerator, pre-sedimentation, coagulation, clearator, filter and reservoir. In the production of drinking water, several problems are encountered that threaten the process. These constraints affect the production target in regard to quality. Minister of Health Regulation No. 492 of 2010 about Requirements for Quality of Drinking Water stated every drinking water provider is obliged to guarantee the drinking water it produces is safe for human health, meeting the quality standards of physical, chemical and biological parameters. This study used Hazard Analysis Critical Control Point method. Hazard Analysis is an analytical method to identify the presence of hazards and risks in the supply production chain so the control management can be established. The existence of hazards in production process will cause losses in terms of economics and also customer trust. This method reviewed based on laboratory results of water quality and the existing conditions of operational in production process. The analysis and evaluation of its existing conditions using HACCP method generates information that the biggest source of risk that affects the quality of production is found in the operations of each processing unit and fluctuations of its debit. The corrective actions that can be taken to prevent the occurrence of failures in the production system are improving the performance of the water treatment units, discharge settings according to unit capacity, there must be modification of the flocculation and aeration process, also improvement of workers' insights regarding water quality in accordance with SNI 01-4852-1998.